THE EFFECT OF ADDITION OF PAPAIN ENZYME ON THE QUALITY AND CHARACTERISTICS OF FRESH-WATER SCALLOP (Pilsbryconcha exilis)SAUCE - D P N Daeli, Jansen; Leksono, Tjipto; Sari, N. Ira (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abtract The study aimed to determine the effect of the addition of the commercial papain enzymes and papaya leaves on the quality and characteristics freshwater scallop sauce. The research was carried out by using the experimental method, by conducting experiments on making of freshwater scallop sauce by adding commercial papain enzymes and papaya leaves. The experimental was designed as the non-factorial Completely Randomized Design (CRD). The treatment given was consisted of 3 levels namely P0 (control), P1 (addition of commercial papain enzyme), P2 (addition of papaya leaves), for 3 replications. The result showed that the addition of commercial papain enzymes and papaya leaves significantly affected to the taste, flavor, protein content and NPN values, but did not affect lactic acid bacteria. The freshwater scallop processed by addition of papaya leaves (P2) was producing the best quality of the scallop sauce, which was shown by the highest organoleptic value. The value of taste was 7.2 with characteristics tasty and quite salty as specific scallop sauce taste, but papaya slightly tasted. The value of aroma was 6.8, characterized by the specific aroma of fermented fresh scallop. Meanwhile, the highest content of protein was produced by the control treatment (P0) at 2.99 %, the highest content of non-protein nitrogen was produced by treatment of the addition of commercial papain enzyme (P1) at 0.74 %, and the highest number of lactic acid bacteria was shown in the product treated by the addition of papaya leaves (P2) at 6.7Keyword: characteristics, enzyme, papain,Pilsbryoconcha exilis,sauce